2012
DOI: 10.1002/lt.23522
|View full text |Cite
|
Sign up to set email alerts
|

Renal dysfunction in liver transplant recipients: Evaluation of the critical issues

Abstract: Major progress has been made in the field of liver transplantation since the first procedure was performed nearly 50 years ago. Despite these improvements, renal dysfunction before and after liver transplantation remains a major complicating factor associated with increased health care costs, morbidity, and mortality. Creatinine-based estimates of renal function are inaccurate in the setting of end-stage liver disease and often lead to underdiagnosis and late intervention. This issue is critical in that it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 61 publications
2
92
1
8
Order By: Relevance
“…However, different studies have shown that the MELD-score predicted neither the development of advanced CKD nor mortality more than one year after LT, 5,12,33,37 which is in agreement with our findings since, even in the univariate analysis, this variable was not associated with CKD stage or mortality, two years post-LT.…”
Section: B Discussionsupporting
confidence: 92%
“…However, different studies have shown that the MELD-score predicted neither the development of advanced CKD nor mortality more than one year after LT, 5,12,33,37 which is in agreement with our findings since, even in the univariate analysis, this variable was not associated with CKD stage or mortality, two years post-LT.…”
Section: B Discussionsupporting
confidence: 92%
“…In addition, there is an increased morbidity associated with renal insufficiency, so it would not be surprising if lower survival rates were observed in patients who underwent CLKT. In fact, if the transplanted kidney works, this can minimize these problems and can be better for the patient than undergoing dialysis after transplantation [2,8,10].…”
Section: Clkt (N=31)mentioning
confidence: 99%
“…Indication to combined procedure is straightforward in patients under dialyses. Conversely, in those patients with potentially reversible kidney failure can be difficult to predict whether the native kidney will recovery sufficiently after LT alone [2,4,7,11]. In our institute, we consider more than 8 weeks of dialysis given at least 2 times per week to indicate the CLKT procedure.…”
Section: Clkt (N=31)mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 lists the most important side effects of the immunosuppressants which are currently available. End-stage renal failure requiring kidney transplantation occurs 10 years after LT (as well as after heart transplantation) in up to 20% of patients, which is, at least in part, caused by the nephrotoxicity of calcineurin inhibitors [18]. In some patients, withdrawal of these drugs and replacement by derivatives of mycophenolic acid or by mTOR inhibitors may be successful.…”
Section: Nonsurgical Issuesmentioning
confidence: 99%